Communication Ethics between Teachers and Students in the Study of the Book of Taisirul Khalaq - Miftachul Ulum; Abdul Mun’im (Jaanur Elbarik Indonesia, 2026)
The purpose of this study is to examine the concept of communication ethics between teachers and students from the perspective of the Taisirul Khalaq book, a classic work that emphasizes the importance of manners, morals, and etiquette in the educational process. This study uses a qualitative approach with a literature study, namely examining the Taisirul Khalaq text and related literature on communication ethics and Islamic education. The results of the study indicate that communication between teachers and students is not merely a transfer of knowledge, but also a process of character formation through role models, respect, and mutual appreciation. The position of teachers as figures who must be honored because of their role as inheritors of the knowledge of the scholars, while students are required to demonstrate an attitude of humility, obedience, and politeness. Teacher ethics in communication include sincerity, gentleness, and patience in guiding students, while student ethics emphasize obedience, respect, and sincerity in seeking knowledge.